Uplink Frequency Offset Solution for LTE-Based High-Speed Railway Telecommunication System - Xiaohong Yu (Dianxin kexue)
Doppler frequency offset can severely impact the performance of uplink in LTE-based high-speed railway telecommunication system. Frequency offset pre-compensation in transmitter combined with residual frequency offset compensation in receiver was proposed to solve this problem. The simulation results demonstrate that this scheme can improve the uplink performance for high-speed railway telecommunication system.